Functional characterization of corA magnesium transporter from thermotoga maritima - Xia, Yu (2010)
Magnesium is the most abundant divalent cation in the cell, and is required for many cellular processes, such as various enzymatic reactions, gene transcription and translation as well as membrane stability. Therefore, the intracellular magnesium concentration must be well-regulated. CorA is a primary magnesium transporter found in both Bacteria and Archaea. Recently, three crystal structures of CorA from Thermotoga maritima have been reported in closed conformation. The structures have helped to indentify some important functional domains such as potential regulatory metal binding sites located at the N-terminal domain. However, the main questions about the transport and regulation of metal ions are still unanswered. Thus, this project aims to provide biochemical data to link structure of TmCorA to function. TmCorAs with mutations at proposed functional sites were employed in this study. D89 was found to be important for metal coordination at M1 site, loop connecting α5- α6 also seemed to have a role in metal coordination, as thermostability results indicated that mutation of these residues had decreased protein stability upon metal binding. In addition, the importance of D253 and loop connecting α5-α6 in metal ion regulation was highlighted by in vivo study. These findings are consistent with the previous structure observations.